Klasifikasi Motif Citra Kain Sutera Bugis Mengunakan Metode Markerless Marker - Abd Gani, Zulfahmiz; Syarif, Syafruddin; Yuyun, Yuyun (Program Studi Teknik Elektro Universitas Khairun, 2020)
Silk is one of the national cultural heritage with various motifs and patterns. This research aims to detect and classify the image of the silk cloth based on motive. This research uses Augemented Reality technology with Markerless Marker Tracking method. To display a 3D object, the proposed method uses a special pattern as a marker to recognize the fabric type. As a research sample, the authors used 10 types of bugis silk motifs. From the test results found that markers can detect fabric motifs in bright rooms and undetectable markers in dim rooms. The best distance in detecting markers is 10 cm Ã¢â‚¬â€œ 50 cm.Ã‚Â Meanwhile at a distance of 110 cm, the marker cannot be detected.